2, 4, 6-Trihydroxy-3-geranyl acetophenone suppresses vascular leakage and leukocyte infiltration in lipopolysaccharide-induced endotoxemic mice. (1st January 2021) - Chan, Yee Han; Musa, Nazmi Firdaus; Chong, Yi Joong; Saat, Siti Arfah; Hafiz, Faizul; Shaari, Khozirah; Israf, Daud Ahmad; Tham, Chau Ling
Abstract: Context: Lipopolysaccharide (LPS) exacerbates systemic inflammatory responses and causes excessive fluid leakage. 2, 4, 6-Trihydroxy-3-geranyl acetophenone (tHGA) has been revealed to protect against LPS-induced vascular inflammation and endothelial hyperpermeability in vitro. Objective: This study assesses the in vivo protective effects of tHGA against LPS-induced systemic inflammation and vascular permeability in endotoxemic mice. Materials and methods: BALB/c mice were intraperitoneally pre-treated with tHGA for 1 h, followed by 6 h of LPS induction. Evans blue permeability assay and leukocyte transmigration assay were performed in mice ( n = 6) pre-treated with 2, 20 and 100 mg/kg tHGA. The effects of tHGA (20, 40 and 80 mg/kg) on LPS-induced serum TNF-α secretion, lung dysfunction and lethality were assessed using ELISA ( n = 6), histopathological analysis ( n = 6) and survivability assay ( n = 10), respectively. Saline and dexamethasone were used as the negative control and drug control, respectively. Results: tHGA significantly inhibited vascular permeability at 2, 20 and 100 mg/kg with percentage of inhibition of 48%, 85% and 86%, respectively, in comparison to the LPS control group (IC50 =3.964 mg/kg). Leukocyte infiltration was suppressed at 20 and 100 mg/kg doses with percentage of inhibition of 73% and 81%, respectively (IC50 =17.56 mg/kg). However, all tHGA doses (20, 40 and 80 mg/kg) failed to prevent endotoxemic mice from lethality because tHGA could not suppress TNF-α overproduction and organ dysfunction. Discussion and conclusions: tHGA may be developed as a potential therapeutic agent for diseases related to uncontrolled vascular leakage by combining with other anti-inflammatory agents.